Analysis of Thermal Decomposition of Solid Rocket Propellants - Marcin CEGŁA; Janusz ZMYWACZYK; Piotr KONIORCZYK (Problemy Mechatroniki)
The paper presents results of thermal decomposition analysis of selected solid rocket propellants. Homogeneous propellant PAC and heterogeneous propellant H2 were subjected to simultaneous thermal analysis with the use of NETZSCH STA 2500 Regulus device with five heating rates of 2.5, 5, 7.5, 10 and 15 K/min. The method combines TG, DTG and DTA analytical techniques in a single measurement. The aim of the conducted experiments was to study thermal decomposition of these energetic materials as well as to determine activation energy of the decomposition process and the preconditioning factor from the TG curves. The tested materials properties and chemical composition along with a brief description of the experimental procedure are described. The inverse procedure of calculating the activation energy, based on the Ozawa-Flynn-Wall model is described. Finally, the results of thermal decomposition of two tested solid rocket propellants are presented along with maximum decomposition rates and percentage of mass loss.